2012
DOI: 10.1371/journal.pone.0033767
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Polymorphisms Associated with Time-on-Task Declines and Fatigue in the Psychomotor Vigilance Test

Abstract: Prolonged demands on the attention system can cause a decay in performance over time known as the time-on-task effect. The inter-subject differences in the rate of this decline are large, and recent efforts have been made to understand the biological bases of these individual differences. In this study, we investigate the genetic correlates of the time-on-task effect, as well as its accompanying changes in subjective fatigue and mood. N = 332 subjects performed a 20-minute test of sustained attention (the Psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 59 publications
(74 reference statements)
5
44
0
Order By: Relevance
“…100 In our study, being homozygous for the rare A allele of SLC6A3 rs37022 was associated with a 9.75-fold higher odds of belonging to the Lower Energy class. No studies were identified that reported on polymorphisms in this SNP.…”
Section: Discussionsupporting
confidence: 46%
“…100 In our study, being homozygous for the rare A allele of SLC6A3 rs37022 was associated with a 9.75-fold higher odds of belonging to the Lower Energy class. No studies were identified that reported on polymorphisms in this SNP.…”
Section: Discussionsupporting
confidence: 46%
“…There was a significant main effect of time on RT (F = 3.101, P = 0.046) but no effect on accuracy (F = 1.034, P = 0.397). In previous studies, RT measures have been associated with fatigue from sustained mental workload [21,22]. In Figure 4, RT increases in a linear fashion from the beginning to the end of task performance (R 2 = 0.69), while there is a mild decline in accuracy.…”
Section: Rt and Accuracymentioning
confidence: 79%
“…In a sample of 100 breast cancer survivors, fatigue was found to be related with the Catechol-O-methyltransferase (COMT) gene [20]. In a sample of 332 healthy university students and staff, time on task and subjective indicators of energy level were evaluated for association with genes governing dopamine [21]. Polymorphisms in COMT and dopamine transporter gene (DAT1) were associated with differences in time taken for task completion while subjective declines in mental energy were associated with dopamine receptor D4 (DRD4) polymorphisms.…”
Section: Resultsmentioning
confidence: 99%